Meningkatkan Hasil Belajar Siswa Dengan Menggunakan Model Pembelaaran Discovery Learning - Rubina Samosir (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The subjects of this study were 10 grade students of SD N 064977 Medan Tembung for the academic year 2020/2021. The subjects of this research are activities during learning and student learning outcomes. The research was conducted for 3 months. The object of this research is the Student Learning Outcomes in the Catholic Religious Education subject, which one of the indicators can be seen in the improvement of speaking skills and reflection in the learning process of students with standards. Classical mastery of learning shows a significant increase in achieving the ideal criteria which indicates the success rate of learning (80%). The number of students who achieved the minimum completeness criteria increased to 8 out of 10 people, namely 80%. The use of the Discovery Learning Model can improve reflection skills and learning outcomes of fourth grade students at SD N 064977 Tembung Medan in PAK Subjects. Keywords: Learning Outcomes, Discovery Learning  Abstrak: Subjek penelitian ini adalah siswa kelas IV SD N 064977 Medan Tembung tahun pelajaran 2020/2021 berjumlah 10 siswa. Subjek penelitian ini adalah kegiatan selama pembelajaran dan hasil belajar siswa. Penelitian dilaksanakan selama 3 bulan. Yang menjadi objek dalam penelitian ini adalah Hasil Belajar Siswa dalam  mata pelajaran Pendidikan Agama Katolik yang salah satu indikatornya dapat dilihat pada meningkatnya keterampilan  berbicara dan berefleksi dalam proses   belajar siswa  dengan Standar. Ketuntasan Belajar secara Klasikal menunjukkan adanya peningkatan yang cukup signifikan yang mencapai kriteria ideal yang menunjukkan tingkat keberhasilan pembelajaran (80 %). Jumlah siswa yang mencapai Kriteria Ketuntasan Minimal meningkat menjadi 8 dari 10 orang, yaitu  sebesar 80 %. Penggunaan Model Discovery Learning dapat Meningkatkan Keterampilan berefleksi dan  Hasil Belajar Siswa Kelas IV SD N  064977 Medan Tembung pada Mata Pelajaran PAK. Kata Kunci : Hasil Belajar, Discovery Learning